Efektivitas Penggunaan Faktor Produksi Usahatani Anggur di Desa Kalianget, Kecamatan Seririt, Kabupaten Buleleng - WIBAWA, GEDE MIKO SATRIA; AGUNG, I DEWA GEDE; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
The Effectiveness of The Usage of Production Factors in Grape Farming at Kalianget Village, Seririt District, Buleleng Regency The existence of grapes in Bali is used as a livelihood for farmers. One of the plantation locations that has a large number of grape vines is Kalianget Village, Seririt District, Buleleng Regency. The purpose of this study was to determine the effectiveness of the use of grape farming production factors consisting of land, seeds, fertilizers, labor and medicine. This research is a quantitative descriptive study by comparing the use of each production factor in grape farming in Kalianget Village with the determination of the use of grape farming production factors from the Agriculture Service. The research sample was 47 grape farmers of Kalianget Village who were selected by purposive sampling technique. Data collection on the effectiveness of the use of farming production factors was carried out with a structured questionnaire and the data were analyzed by Microsoft Excel computer program. The results of this study indicate that the effectiveness of the use of grape farming production factors in Kalianget Village, namely manure, NPK, zpt and fungicides is classified as effective. While the use of urea, insecticides and labor is classified as ineffective. The use of several factors in grape farming production is oriented to good and correct cultivation techniques and there are some farmers who cannot implement it. This is because farmers do not have enough knowledge, skills and information about good and true wine cultivation. It is expected that farmers in carrying out agricultural activities to be more careful in the use of production factors and for the government are expected to pay attention to horticultural products, especially wine.